Comparative Analysis of Hotel Cost Efficiency Across Indonesian Regions - Abdul Ghofur; Hendri Kurniawan; Ahmad Muthohar; Dyah Palupiningtyas (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
The Indonesian hospitality industry is currently facing a post-pandemic